Sensitivity of Total Column Ozone to Stratospheric Sulfur Injection Strategies. Issue 19 (10th October 2021) - Tilmes, S.; Richter, J. H.; Kravitz, B.; MacMartin, D. G.; Glanville, A. S.; Visioni, D.; Kinnison, D. E.; Müller, R.
Abstract: We explore the impact of different stratospheric sulfur injection strategies to counter greenhouse gas induced warming on total column ozone (TCO), including high and low altitude injections at four latitudes, equatorial injections, and using a configuration with higher vertical resolution, based on a state‐of‐the‐art Earth system model. The experiments maintain global surface temperatures at 2020 conditions, while following the unmitigated future scenario. Within the first 10 years of the injection, we find an abrupt deepening of the Antarctic ozone hole by 8%–20% and changes up to ± 5% for other regions and seasons. The ozone hole recovery is delayed by ∼25 to over 55 years, with the fastest recovery for low‐altitude injections and slowest for equatorial injections. Mid to high‐latitude TCO increases by ∼ 15% in Northern Hemisphere winter and spring between 2010–2019 and 2080–2089 due to both increasing greenhouse gases and increasing sulfur injections. Implications for ecosystems need to be investigated. Plain Language Summary: Stratospheric aerosol intervention (SAI) has been proposed to counter greenhouse gas induced warming. Different sulfur injection strategies have been studied to limit some of the known side effects of SAI on the surface climate. Here we explore the effects of these sulfur injection strategies on total column ozone (TCO) including effects on the recovery of the Antarctic ozone hole. We show that even a slow phase‐in of sulfur injections is leading to an abrupt deepening of the Antarctic ozone hole in the first 10 years, reducing TCO by 8%–20% depending on the injection strategy. Other regions experience a moderate change of ± 5% in TCO. After 10 years, using a non‐mitigated future scenario, TCO follows the recovering trend of the control simulation, delaying the ozone recovery by 25 to over 55 years. In the Northern Hemisphere winter and spring SAI results in an increase of TCO and, combined with the effects of climate change, a ∼15% total increase. Both decreasing and increasing trends of TCO for different regions and periods are expected to impact ecosystems, which has to be investigated. Key Points: Onset of stratospheric sulfur injection results in an abrupt deepening of the Antarctic ozone hole in the first 10 years The ozone hole recovery is delayed by ∼25 to over 55 years, with the fastest/slowest recovery for low‐altitude/equatorial injections Stratospheric sulfur injection can lead to an increase in column ozone in tropics and mid‐latitudes